Knowledge, attitude and practice (kap) of dengue fever prevention among community in Kampung Demit and Kampung Bayam, Kubang Kerian, Kelantan - Eva Nabiha, Zamri (PPSP, Universiti Sains Malaysia, 2009)
Nowadays, dengue fever becomes one of the important public health problems to international public health and in Malaysia (Poovaneswari, 1993). The only effective measure available to prevent and control dengue is by preventing transmission of the disease by the Aedes mosquito require support, cooperation and participation by the community. Therefore, it is vital to know the level of knowledge, attitude and the practices (KAP) of the community concerning the disease. A cross sectional study was conducted to assess the level of knowledge, attitudes and practices among selected communities in Kubang Kerian district which are Kampung Demit and Kampung Bayam. The number of targeted sample are (n=253) but only I 02 respondents achieved. The finding shows that overall the researcher can conclude that both villages had good knowledge (51%) good attitude (100%) but medium practice (69.6%) related to prevention of Aedes. From the results, it can be concluded that the demographic background which are age, sex, educational level do not influence the level knowledge, practice and attitude among community in Kampung Demit (p> 0.05). Meanwhile in Kampung Bayam, demographic background which are age and sex does not influence the level of knowledge and practice related to dengue fever where p-value > 0.05. But level of education influence the level of knowledge and practice among community in Kampung Bayam where p- value = 0.0 1. There is no significant association level of knowledge, attitude and practice related to dengue fever prevention between community in Kampung Demit and Kampung Bayam (p>O.OS). Outcome of this research also stated that there is a significant correlation between level of knowledge and level of practice, level of knowledge and level of attitude and also level of practice and level of attitude related to dengue fever prevention among community in Kampung Demit and Kampung Bayam (p<0.05). As the conclusion, it is recommended that a change in the approach of the health education program emphasize and improving the practice related to dengue prevention among community.